2019
DOI: 10.1111/plb.13019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of a novel FT orthologous gene in London plane with a distinct expression response to environmental stimuli compared to PaFT

Abstract: FLOWERING LOCUS T (FT) is a key integrator of environmental signals and internal cues, and codes for florigen-like activity which regulates the transition from vegetative to reproductive growth in flowering plants. Unlike annual plants, perennial tree species undergo several years of vegetative growth prior to the transition to the reproductive stage, as characterised by the ability to form flower buds. Thereafter, trees in temperate regions typically display an annual growth cycle involving distinct vegetativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In addition, some PaBBX genes were regularly expressed, corresponding to different stages of dormancy and bud break. Previous studies have shown that the expression of PaFT dramatically increased under low temperatures and short days from early autumn to late winter and was believed to serve to release buds from dormancy [27]. Expression patterns of PaBBX8-1, PaBBX8-2, PaBBX9-1, PaBBX28/29-1, and PaBBX32-2 were similar to these of PaFT, suggesting that these genes may act as an upstream regulator of PaFT to contribute to the break of dormancy.…”
Section: Expression Patterns and Potential Functions Of Pabbx Genesmentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, some PaBBX genes were regularly expressed, corresponding to different stages of dormancy and bud break. Previous studies have shown that the expression of PaFT dramatically increased under low temperatures and short days from early autumn to late winter and was believed to serve to release buds from dormancy [27]. Expression patterns of PaBBX8-1, PaBBX8-2, PaBBX9-1, PaBBX28/29-1, and PaBBX32-2 were similar to these of PaFT, suggesting that these genes may act as an upstream regulator of PaFT to contribute to the break of dormancy.…”
Section: Expression Patterns and Potential Functions Of Pabbx Genesmentioning
confidence: 75%
“…Platanus × acerifolia is a perennial deciduous tree undergoing a flowering transition in mid to late spring. This is followed by vegetative growth in summer, then enters dormancy in early autumn to late winter, and subpetiolar bud breaks in early spring [27,28]. Previous studies have revealed that two FT orthologs, which may act as downstream targets of BBX homologous genes, are responsible for regulating flowering and/or dormancy in P. × acerifolia, respectively [27,29,30].…”
Section: Of 20mentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, PaFT has been shown to display increased expression levels in response to LT/SD in London plane trees 43 . Moreover, PaFTL, another FT orthologous gene in London plane trees, showed low and variable expression levels during dormancy and under LT/SD conditions 44 .…”
Section: Introductionmentioning
confidence: 99%